Optimal allocation of phase shifting transformer with uncertain wind power based on dynamic programming - Fu, Kang; Du, Zhaobin; Li, Feng; Li, Zuohong; Xia, Chengjun (Frontiers in Energy Research, 2023)
Phase Shifting Transformer (PST) can help improve the power flow distribution of the transmission lines, which would result in increased wind power consumption when PST are installed in the grids with wind power. In order to adapt the allocation of the PST to the evolution of the grid, this paper presents a dynamic programming method to optimally allocate PST in continuous planning grids with uncertain wind power. The optimal allocation model of PST under a single grid seeks to maximize the wind power consumption and the Total Transfer Capacity(TTC) between areas, and a calculation method for TTC of grids containing PST and wind power is proposed. The Non-Dominated Sorting Genetic Algorithm II (NSGA2) is improved to solve the Pareto sets under each planning grid, and then the optimal planning path of PST under continuous planning grids is derived based on dynamic programming. The superiority of the proposed method is demonstrated by comparing the IEEE-118 system results of dynamic and static programming.